1996
DOI: 10.1007/bf02282885
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance, pharmacokinetics and efficacy of once daily amikacin for treatment of Pseudomonas aeruginosa pulmonary exacerbations in cystic fibrosis patients

Abstract: Once daily amikacin administration associated with ceftazidime is well tolerated for the treatment of Pseudomonas aeruginosa pulmonary exacerbations in cystic fibrosis patients. Serum peak levels and diffusion in sputum are higher than with a conventional schedule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 15 publications
2
35
1
Order By: Relevance
“…The serum pharmacokinetics of tobramycin did not change between day 1 and day 14, indicating that there was no accumulation of the drug during treatment. In contrast with our previous study with once daily amikacin,11 we observed a large interindividual variation in serum peak tobramycin, not only in the thrice daily group but also in the once daily group. There was a high sputum concentration of tobramycin early after the end of the infusion.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The serum pharmacokinetics of tobramycin did not change between day 1 and day 14, indicating that there was no accumulation of the drug during treatment. In contrast with our previous study with once daily amikacin,11 we observed a large interindividual variation in serum peak tobramycin, not only in the thrice daily group but also in the once daily group. There was a high sputum concentration of tobramycin early after the end of the infusion.…”
Section: Discussioncontrasting
confidence: 99%
“…We previously showed in an open study that 35 mg/kg amikacin given as a once daily infusion, combined with 200 mg/kg/day of ceftazidime in three daily injections, was a well tolerated and effective treatment of Ps aeruginosa exacerbations in cystic fibrosis 11. This study aimed to compare efficacy, tolerance, and serum and sputum pharmacokinetics of once daily versus thrice daily tobramycin, combined with ceftazidime, in a population of young cystic fibrosis patients.…”
mentioning
confidence: 99%
“…No aminoglycosides in CF that describes nephrotoxicity [16][17][18][19][20][21][22][23][24]. There was no significant change in serum creatinine or magnesium with treatment in either group in this study.…”
Section: Resultsmentioning
confidence: 85%
“…This likely reflects the availability of well-designed safety and efficacy studies and meta-analyses evaluating tobramycin EID in this population, and the lack of published research studies assessing the use of gentamicin and amikacin EID in those with CF. 10,11,[13][14][15][16][17][18] As in the pediatric CF population, empiric dosing of tobramycin was most commonly prescribed at 10 mg/kg/d. 19 This practice is consistent with the dose used in a large, randomized, controlled, noninferiority study published in 2005.…”
Section: Discussionmentioning
confidence: 99%
“…8 In light of the emergence of safety and efficacy data in the CF population, the Cystic Fibrosis Foundation deemed once-daily aminoglycoside dosing as acceptable for Pseudomonas aeruginosa (grade C recommendation) in its September 2009 pulmonary exacerbation guidelines. [9][10][11][12][13][14][15][16][17][18] A 2009 survey of United States pediatric CF centers and affiliate programs distributed after the publication of these guidelines reported the use of EID (with once-daily or twice-daily dosing) in the pediatric CF population to be 94%, a significant increase from previous reports. 19 While empiric evidence suggests the use of EID of aminoglycosides to be increasingly common in the United States CF population, the prevalence of EID use across United States adult CF centers as well as the dosing and monitoring practices associated with this regimen following publication of the CF pulmonary exacerbation guidelines remain to be elicited.…”
Section: Introductionmentioning
confidence: 99%